MENUMBUHKAN NILAI-NILAI KEARIFAN LOKAL MELALUI KARYA TARI KOREOGRAFER PEREMPUAN DI SUMATERA BARAT: SUATU TINJAUAN GENDER - Astuti, Fuji (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2016)
DEVELOPING LOCAL WISDOM VALUES THROUGH THE DANCE WORKS OF FEMALE CHOREOGRAPHERS IN WEST SUMATERA: A GENDER STUDIES Minagkabau in the social order, the personality of a woman governed by a norm that is contained in the content of the values of sumbang duo baleh (the twelfe of improper behaviors). As a female choreographer, the values of sumbang duo baleh are not only seen in the attitude of her personality, but also in the content her dance work as a reflection of her personality. However, all the twelfe values cannot considered altogether in a dance. If all the content of those values are fully referenced in the dance work, choreographers feels such rules would hamper creativity, especially in the embodiment of motion to the media staple in dance. The values of twelfe improperly behaviors can be implemented into the dance are walk improperly, sit improperly, stand improperly, look improperly, improper clothing, and improper behaviors. On the other hand, the involvement of women in artistic activity, driven by the demands of the economy. For that reason, women no longer have to rely on the man as the leader of the household, or be the responsibility of the system as in the economy in the longhouse, yet can already be anticipated through achievement in art. It likewise trigger the choreographer seeks to meet the needs of consumers, even vying to create markets that are commercial.Key words: The twelfe lacks, choreographer, dance AbstrakDalam tatanan sosial masyarakat Minagkabau, kepribadian seorang perempuan diatur oleh suatu norma yang tertuang dalam kandungan nilai-nilai sumbang duo baleh. Sebagai seorang koreografer perempuan, kandungan sumbang duo baleh tidak hanya terlihat dalam sikap kepribadiannya, namun kandungan nilai-nilai itu juga dapat terlihat dalam karya tari sebagai cerminan kepribadiannya. Kandungan nilai sumbang duo baleh tidak semuanya dapat dituangkan dalam karya tari. Jika semua kandungan nilai-nilai tersebut secara utuh dijadikan acuan dalam berkarya tari, koreografer merasakan aturan-aturan tersebut akan menghambat kreativitas, terutama dalam perwujudan gerak yang menjadi media pokok dalam tari. Adapun kandungan nilai sumbang duo baleh dengan lugas dapat diimplementasikan ke dalam tari adalah sumbang jalan, sumbang duduak, sumbang tagak, sumbang penglihatan, sumbang pakaian, dan sumbang kurenah. Di sisi lain, keterlibatan perempuan dalam aktivitas kesenian, didorong oleh tuntutan perekonomian. Untuk itu, perempuan tidak lagi harus menggantungkan perekonomian sepenuhnya kepada laki-laki sebagai pemimpin rumah tangga, atau menjadi tanggung jawab kaum sebagaimana dalam sistem perekonomian di rumah gadang, namum sudah dapat diantisipasi melalui prestasi dalam berkesenian. Hal demikian pula memicu para koreografer berupaya memenuhi kebutuhan konsumen, bahkan berlomba-lomba untuk menciptakan pasar yang sifatnya komersil.Kata Kunci: Sumbang duo baleh, koreografer, tari